Pelaksanaan Layanan Bimbingan Dan Konseling Oleh Guru Kelas Di Sdit Smart Cendekia Karanganom Klaten - Nilasari, Putri; , Minsih, S.Ag., M.Pd (2017)
Task classroom teachers besides teaching BK is providing services to all the students who are responsible. This study aims to describe the implementation of guidance and counseling services by the class teacher in SDIT Smart Cendekia Karanganom Klaten and obstacles that come along with the solution. This study is a qualitative research with case study design. Based on the results of this study concluded that the implementation of guidance and counseling services in SDIT Smart Cendekia Karanganom Klaten as follows: service orientation is given at the beginning of his new students entering grade / early years / current MOS. Service information provided is information about healthy living, a way of communicating that is good and right, prepare students to take the test / exam, and information requirements grade / pass and the effects of failing a grade / pass. Placement and distribution services that briefing if there are students who are confused in choosing extracurricular and form groups. Learning services, individual counseling and group counseling is given conditionally. Service group guidance given at the time students are in one group. Barriers of implementation of guidance and counseling services by the class teacher comes from internal factors (personal teacher and curriculum) and external factors (students and parents). Solutions to overcome the obstacles that classroom teachers should receive training, develop curricula SD BK it self, and classroom teachers provide insight to students and parents.